Future Swiss Energy Economy: The Challenge of Storing Renewable Energy - Züttel, Andreas; Gallandat, Noris; Dyson, Paul J.; Schlapbach, Louis; Gilgen, Paul W.; Orimo, Shin-Ichi (Frontiers in Energy Research, 2022)
The resources of fossil fuels and materials on Earth are finite, and the disposal of waste into the air, on land, and into water has an impact on our environment on a global level. Using Switzerland as an example, the energy demand, the technical challenges, and the economic feasibility of a transition to an energy economy based entirely on renewable energy was analyzed. We considered three energy systems i.e. (i) a purely electric system with battery storage (ELC), (ii) hydrogen (HYS), and (iii) synthetic hydrocarbons (HCR) for the complete substitution of fossil fuels in Switzerland with renewable energy produced by photovoltaics. ELC is the most energy efficient solution, however, due to the amount of batteries necessary and the capital cost it is not a feasible solution and the seasonal storage of electricity in pumped hydropower has a big impact on the environment. The HYS allows the hydrogen to be stored underground and requires building of a hydrogen infrastructure and applications working with hydrogen. Finally, the HCR requires the largest photovoltaic (PV) field, but the infrastructure and the applications already exist. The model for Switzerland can be applied to other countries, adapting the solar irradiation, the energy demand and the storage options.